2015
DOI: 10.1085/jgp.201511375
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione release through connexin hemichannels: Implications for chemical modification of pores permeable to large molecules

Abstract: The cytosolic reducing agent glutathione can reverse thiol modification of cysteine residues inside the pores of connexins and other channels permeable to large molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…The relevance of this finding remains unclear. Alternatively, cytosolic GSH may be liberated through Cx32 and Cx43 hemichannels, thus jeopardizing anti-oxidant cellular defense (Keleva et al 2013; Rana and Dringen, 2007; Tong et al, 2015). However, the results of the current study do not seem in line with this scenario, as no differences were found in GSH amounts between the different experimental groups after 3 and 24 hours (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of this finding remains unclear. Alternatively, cytosolic GSH may be liberated through Cx32 and Cx43 hemichannels, thus jeopardizing anti-oxidant cellular defense (Keleva et al 2013; Rana and Dringen, 2007; Tong et al, 2015). However, the results of the current study do not seem in line with this scenario, as no differences were found in GSH amounts between the different experimental groups after 3 and 24 hours (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the latter, Igarashi and group found less decreased GSH and GSSG levels in APAP-treated Cx32 knock-out mice and attributed the protective effect of Cx32 against liver injury to changes in GSH transmission between hepatocytes (Igarashi et al 2014). GSH indeed is known to permeate gap junctions and it has been reported that hemichannels, including those based on Cx32, can also transport GSH (Rana and Dringen 2007; Tong et al 2015). At the more upstream mechanistic platform of APAP toxicity, cell death results from protein adduct formation involving NAPQI.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that connexin hemichannels are permeable to glutathione (GSH) (Slavi et al, 2014;Stridh et al, 2008;Tong et al, 2015). Given that the GSH concentration in vitreous humor is unusually high and hemichannels transport molecules with sizes no more than 1 kDa, we tested the hypothesis that opening of hemichannels in response to oxidative stress facilitates entry of GSH into the cell and protects cells against oxidative damage.…”
Section: Hemichannels Mediate Cellular Uptake Of Glutathione and Protmentioning
confidence: 99%